Otoprotection Mechanisms Against Oxidative Stress Caused by Cisplatin - Gonçalves, Maiara Santos; Silveira, Aron Ferreira da; Murashima, Adriana de Andrade Batista; Rossato, Maria; Hippolito, Miguel Angelo (International Archives of Otorhinolaryngology, 2020)
Introduction Cisplatin damages the auditory system and is related to the generation of free radicals. Glutathione peroxidase is an endogenous free radicals remover.Objective To investigate the mechanisms involved in otoprotection by N-acetylcysteine through the expression of glutathione peroxidase in outer hair cells from rats treated with cisplatin.Methods Male Wistar rats were intraperitoneally injected with cisplatin (8 mg/Kg) and/or received oral administration by gavage of N-acetylcysteine (300 mg/Kg) for 3 consecutive days. On the 4th day, the animals were euthanized and beheaded. The tympanic bullae were removed and prepared for scanning electron microscopy and immunofluorescence.Results Among the groups exposed to ototoxic doses of cisplatin, there was an increase in glutathione peroxidase immunostaining in two groups, the one exposed to cisplatin alone, and the group exposed to both cisplatin and N-acetylcysteine.Conclusion The expression of glutathione peroxidase in the outer hair cells of rats exposed to cisplatin showed the synthesis of this enzyme under cellular toxicity conditions.
Keywords: cisplatin; toxicity; free radicals; cochlea; oxidative stress